Transformational Leadership in the Territorial Development of the Indonesian National Army in Makassar City - Gumay, Lizardo (KnE Social Sciences, 2025)
Territorial development is one of the strategic pillars of the Indonesian Army in creating stability and strengthening national resilience, especially in complex and heterogeneous urban areas. This study aims to analyze transformational leadership in the territorial development of the Indonesian National Army in Makassar City. The research method uses a qualitative approach. Data were collected through interviews, observations, and documentation studies. Research informants include leaders and staff of Kodim, Danramil, and Babinsa as well as the community. Data analysis has been done by interactive analysis, consisting of stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study showed that in the idealized influence indicator, commanders and officers demonstrated exemplary behavior through direct involvement in social community activities. In the inspirational motivation aspect, the Kodim leadership conveyed a message of nationalism and the spirit of defending the country through counseling activities and joint roll calls, but accessibility to all levels of society still needs to be improved. In the intellectual stimulation indicator, there was a communication that encouraged community participation in the coaching program, but it was not optimal. Finally, in the individualized consideration aspect, a personal approach to the community has been carried out, but limited personnel and time are challenges so it has not been implemented effectively.